Recent advancements in surface modifications of dental implants: systematic review - Ayousha Iqbal; Komal Arshad; Maria Shakoor Abbasi; Maryam Maqsood; Ruqaya Shah; Majida Rahim (Journal of the Pakistan Medical Association, 2021)
Implantology is one of the most investigated topic in modern dentistry, This review is aimed to systematically summarize all the industrial, mass production and experimental trends in dental implant manufacture relative primarily to their surface modification over the last year. Research was conducted in Army Medical college, NUMS, Rawalpindi, Armed forces institute of dentistry, CMH, Rawalpindi, Foundation University college of Dentistry, FFH, DHA, Islamabad and the HEC Library, HEC, Islamabad. Literature was searched on PubMed, SCOPUS, MEDLINE, Cochrane and Science direct. The key words employed were “dental Implants”, “surface modification”, “surface morphology”, “surface treatment” and “surface augmentation”. A total of 38 articles were short listed and reviewed in detail. There is abundant evidence suggesting the importance of these surface modification on improving the implant success. Several strategies have been suggested to modify the implant surface topography as well as surface chemistry in order to achieve a micro-porous structure with nano scale architecture, with increased bio activity; hydrophilicity and anti-bacterial properties. There is commendable success with many of these strategies in the lab. However, following the lab success in ex vivo studies, very few of these surface modalities have found their way to clinical set-ups. Key Words: Dental Implants, surface modification, surface morphology, Continuous...